Petroleum refinery wastewater treatment: A pilot scale study. (December 2016) - El-Naas, Muftah H.; Surkatti, Riham; Al-Zuhair, Sulaiman
Highlights: A three-step wastewater treatment process was scaled-up to a Pilot Plant (PP). The PP included electrocoagulation, biodegradation and adsorption steps. The PP was designed to treat 1 m 3 /h of highly contaminated refinery wastewater. The overall PP performance was similar to that of the lab scale process. The PP achieved 96% reduction of COD and 100% reduction of phenol and cresols. Abstract: A three-step pilot plant was designed, fabricated and tested for the treatment of highly contaminated petroleum refinery wastewater. The three-step process consisted of an electrocoagulation (EC) unit, a biological treatment in a spouted bed bioreactor (SBBR) using immobilized Pseudomonas putida in PVA particles, and an adsorption process using granular activated carbon in a packed column. The pilot plant was operated for a period of ten months at a flow rate of 1 m 3 /h, with continuous runs lasting up to 12 h. Different arrangements of the three units were tested to determine the most effective sequence. Placing the EC unit as the pretreatment step resulted in the best performance, since it reduced the COD and suspended solids, and consequently enhanced the performance of the succeeding biodegradation and adsorption units. At the optimum conditions and unit arrangement, the pilot plant was able to reduce the COD by 96% and the concentrations of phenol and cresols by nearly 100%.